The Food Industry And The Manipulation Of The Masses Through Advertising - dos Santos, Ingrid Aparecida Martins; Milani, Cássia Ellen; Belin, Rosangela Aparecida Filiol (Seven Editora, 2023)
The food industry emerged in the 17th century, after the Industrial Revolution, and gained strength with globalization and the rise of capitalism in the 1990s. This was due to the new shape of society, which went from being primarily agrarian and pastoral, with a lifestyle that followed the patterns of nature, to almost completely urban, with a modified and much more accelerated notion of time. The growing charge for productivity, at first in factory jobs, and now in large companies, has caused adaptations in people’s lives, and thus eating habits have also changed, becoming more practical and, consequently, less conscious. Alienation, lack of free time, and stress form the perfect scenario for the food industry to sell its products, even though they are harmful to the consumers’ health. Advertising has become the main driver of industrialized products, selling a distorted image that manipulates the buyers’ choice. Neuromarketing strategies, chromatic scales, slogans, music, and packaging with images of famous characters and artists divert the attention from the controversial ingredients, making the person not know what he or she is consuming. The use of substances with high addictive power, such as sugar, fat, sodium and chemical additives create dependency in the body, leading the consumer to always seek that food, in larger quantities and more often. All this causes the food industry to create its own consumer market, in a cycle that is only possible to escape with awareness, food education, and especially a critical sense, so that the population can choose what to eat freely and consciously, knowing the impacts of their decisions. DOI: https://doi.org/10.56238/colleinternhealthscienv1-106